Influences of track and rolling stock parameters on the railway load amplification factor. (May 2016) - Sadeghi, Javad; Shoja, Sohrab
In conventional design methods for railway tracks, the axle load is multiplied by a term called the load amplification factor (LAF). This operation is performed to compensate for the error introduced into the design process by the assumption of static loads. This approach simplifies the design methods and provides a sufficient level of accuracy. However, the available mathematical expressions proposed for this factor have two significant limitations: they account for a limited number of influencing parameters; and they were developed based solely on the design criteria of the rail. This research aims at improving the current LAF formulation by addressing these two limitations. Mathematical expressions were developed for the correlations between the LAF and influencing parameters due to the track and rolling stock. These expressions cover the design criteria of the track's substructure components (the rail, sleeper and ballast) and include most of the track and rolling stock parameters omitted in the previously developed LAF formulations. The results obtained in this research pave the way towards a more profound understanding of the dynamic response of tracks and provide practical guidance on how to improve the current methods used in railway track analysis and design.